Design, Synthesis and in vitro Evaluation of Phthalimide-Anhydride Derivatives as MMP-9 Suppressors in Breast Cancer Therapy - Tiple, Shital D.; Puranik, Manisha P.; Kar Mahapatra, Debarshi (Asian Journal of Chemistry, 2026)
A novel series of substituted acetic 2-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)anhydride derivatives (5a-e) was designed and evaluated as potential matrix metalloproteinase-9 (MMP-9) suppressors for breast cancer therapy. Molecular docking using Schrödinger Maestro 2021 (PDB ID: 6ESM) revealed effective chelation of the catalytic Zn2+ ion by all derivatives, with the highest Glide score of -5.900 kcal/mol for compound 5a and a promising -4.632 kcal/mol for lead candidate 5c [acetic 2-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)-3-phenylpropanoic anhydride]. Molecular dynamics simulations confirmed the compound 5c–MMP-9 complex stability (RMSD: 1.5-2.5 Å over 100 ns). SwissADME predictions indicated drug-like properties, including high gastrointestinal absorption, compliance with Lipinski’s rule of five and no AMES mutagenicity or hERG inhibition. Compounds were synthesised via a two-step protocol involving phthalic anhydride condensation with amino acids followed by acetyl chloride-mediated cyclodehydration, affording yields of 46-65% (compound 5c: 65%). In vitro, compound 5c exhibited moderate cytotoxicity against MCF-7 breast cancer cells (IC50 = 27.89 µg/mL; 82.7 µM), approaching that of 5-fluorouracil (IC50 = 8.6 µg/mL; 66.1 µM) in the same assay system. Flow cytometry showed that compound 5c induced early apoptosis (30.6% vs. 9.3% controls) and little necrosis. ELISA tests indicated that there was a concentration-dependent reduction of MMP-9 in TPA-stimulated MCF-7 cells (64.36% at a concentration of 55.89 µg/mL, 165.7 µM). Acute oral toxicity in rats gave an LD50 cut-off of 5-50 mg/kg (GHS Category 2), limiting the therapeutic window and requiring further optimisation before preclinical development. The phthalimide-anhydride scaffold offers a promising Zn2+-chelating motif with potential selectivity over hydroxamates. Compound 5c merits further lead optimisation, with in vivo efficacy, pharmacokinetics and selectivity against other MMPs requiring evaluation.